Relasi Gender dalam Keragaman Qira'at - Fakhrudin, Ali (SUHUF, 2010)
Knowledge ofÃ‚Â  qirÃ„ÂÃ¢â‚¬â„¢atÃ‚Â  until now has only been regarded as under-standing the various methodologies used in reciting the Quran. There has been very little research into analyzing the implications of recitative differences in terms of their purpose, although the many versions of qiraÃ¢â‚¬â„¢at rightly give rise to differing exegesis. This paper seeks to examine the implication of QurÃ¢â‚¬â„¢anic recitation in those religious verses that concern gender relations. There are many religious verses that address gender differences but this paper only examines verses connected with the opposite sexes shaking hands and permission for women to work outside the home.Ã‚Â  This second verse is mentioned because until now there has often been the viewpoint that women ought not work outside the home as long as men and women shake hands at the beginning and end of business matters. For that reason, this paper is very suitable for analysis as a reminder that very rarely is there a person who interprets the QurÃ¢â‚¬â„¢an from an angle of familiarity with various qiraÃ¢â‚¬â„¢at.